Quality of Life Profile of NPC Patients at ENT-HNS Department of RSUP Dr. M. Djamil Padang - Iffah Nisrina Reyatri; Sukri Rahman; Lili Irawati (Jurnal Otorinolaringologi Kepala dan Leher Indonesia, 2026)
Quality of Life Profile of NPC Patients at ENT-HNS Department of RSUP Dr. M. Djamil Padang Background: Nasopharyngeal carcinoma (NPC) and its treatment modalities, such as chemotherapy and radiotherapy, can impact various aspects of life, thereby affecting the patient's quality of life (QoL). This study aims to determine the QoL profile of NPC patients at the ENT-HNS Department of Dr. M. Djamil General Hospital, Padang. Methods: The study design used a quantitative descriptive approach. Primary data collection was conducted subjectively using questionnaires from the European Organization for Research and Treatment of Cancer (EORTC): the general QoL instrument (QLQ-C30) and the head and neck cancer-specific module (QLQH&N43), administered through interviews with NPC patients. Results: The majority of patients were male (67.4%), aged 25–64 years (89.1%), and at an advanced stage (80.4%). The majority had undergone or were undergoing concurrent chemoradiotherapy (43.5%). The worst QoL scores from the QLQ-C30 questionnaire were observed advanced-stage patients (QoL 63.96±16.44; functional 62.86±22.98; symptom 41.07±25.64) and patients before therapy (QoL 59.37±17.50; functional 58.29±62.85; symptoms 51.47±18.61). The worst QoL scores from the QLQ-H&N43 questionnaire were found in advanced-stage patients (multi-item 37.06±20.35; single item 36.42±24.18) and patients who had undergone and/or were undergoing concurrent chemoradiotherapy (multi-item 41.80±16.60; single item 39.76±22.08). Conclusion: Disease stage and treatment status significantly influencing QoL in NPC patients. General QoL was lower among advanced-stage and patients before therapy, whereas head and neck-specific complaints were more severe in advancedstage patients and those who had completed or were undergoing therapy.